2019
DOI: 10.1038/s41598-019-46475-3
|View full text |Cite
|
Sign up to set email alerts
|

Population density and water balance influence the global occurrence of hepatitis E epidemics

Abstract: In developing countries, the waterborne transmission of hepatitis E virus (HEV), caused by HEV genotypes 1 (HEV-1) and 2 (HEV-2), leads to the onset of large recurrent outbreaks. HEV infections are of particular concern among pregnant women, due to very high mortality rates (up to 70%). Unfortunately, good understanding of the factors that trigger the occurrence of HEV epidemics is currently lacking; therefore, anticipating the onset of an outbreak is yet not possible. In order to map the geographical regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…In our study (which was not a seroprevalence study), a higher incidence (34% versus 21% of the febrile jaundice cases) was found in Bangui compared to the rest of the country. This might be due to the higher population density in Bangui with water supplies that are shared by a lot of people [2]. However, the incidence in the rest of the country was far from negligible with detected strains that are closely related to strains isolated in Bangui.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our study (which was not a seroprevalence study), a higher incidence (34% versus 21% of the febrile jaundice cases) was found in Bangui compared to the rest of the country. This might be due to the higher population density in Bangui with water supplies that are shared by a lot of people [2]. However, the incidence in the rest of the country was far from negligible with detected strains that are closely related to strains isolated in Bangui.…”
Section: Discussionmentioning
confidence: 98%
“…Hepatitis E virus (HEV) infection represents a significant public health problem in many parts of the world, particularly in Africa where it can cause outbreaks of acute hepatitis in areas with a high population density, heavy seasonal rainfall and high evapotranspiration rates [1,2]. HEV has two epidemiological profiles in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Acute HEV infection with genotype 1 or 2 is a frequent cause of acute hepatitis and jaundice in many parts of the world because of spread of the virus through fecal–oral transmission ( 1 , 2 , 24 ). By contrast, cases arising from HEV genotypes 3 and 4 infection are zoonotic and account for most autochthonous HEV infections in European countries where pigs and wild boar are the main reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic outbreaks have also occurred in recent years in Asian and African countries, but with a low number of reported cases [ 133 , 134 , 135 , 136 , 137 ]. Using modelling approaches, a recent study describes the ecologically most suitable hotspots for HEV viruses: the Ganges Valley in India and Pakistan [ 138 ]. Important factors contributing to water-related outbreaks of HEV are population density, socio-economic conditions, the level of sanitation, and access to drinking water [ 14 , 138 ].…”
Section: Outbreaksmentioning
confidence: 99%
“…Using modelling approaches, a recent study describes the ecologically most suitable hotspots for HEV viruses: the Ganges Valley in India and Pakistan [ 138 ]. Important factors contributing to water-related outbreaks of HEV are population density, socio-economic conditions, the level of sanitation, and access to drinking water [ 14 , 138 ]. There are also frequent outbreaks in refugee camps, military camps, and emergency shelters in conflict- and catastrophe-affected regions [ 127 , 139 , 140 , 141 , 142 ].…”
Section: Outbreaksmentioning
confidence: 99%